Effect of aluminium content and processing parameters on the microstructure and mechanical properties of laser powder-bed fused magnesium-aluminium (0, 3, 6, 9wt%) powder mixture. Issue 4 (13th May 2019) - Niu, Xiaomiao; Shen, Hongyao; Xu, Guanhua; Zhang, Linchu; Fu, Jianzhong; Deng, Xiaolei
Abstract : Purpose: Mg-Al powder mixture was used to manufacture Mg-Al alloy by laser powder bed fusion (LPBF) process. This study aims to investigate the influence of initial Al content and processing parameters on the formability, microstructure and consequent mechanical properties of the laser powder bed fused (LPBFed) component. Design/methodology/approach: In this study, Al powder with different weight ratio ranged from 3 to 9 per cent was mixed with pure Mg powder, and the powder mixture was processed using different LPBF parameters. Microstructure and compressive properties of the LPBFed components were examined. Findings: It was found that the presence of Al significantly modified the microstructure and improved the mechanical properties of the LPBFed components. Higher volume of ß-Al12Mg17 precipitates was produced at higher initial Al content and higher laser energy density. For this reason, the a-Mg was significantly refined and the compressive strength was improved. The highest yield compressive strength achieved was 279 MPa when using Mg-9 Wt. % Al mixture. Originality/value: This work demonstrates that LPBF of Mg-Al powder mixture was a viable way to additively manufacture Mg-Al alloy. Both Al content and processing parameters can be modified to control the microstructure and mechanical properties of the LPBFed components.